The The Relationship Between Self-Concept and Assertive Behavior in Adolescents at Ar-Rudho Junior High School, East Jakarta - Dhamarani, Aldha; Khoirunnisa, Riza Noviana (Character Jurnal Penelitian Psikologi, 2023)
This study aims to determine the relationship between self-concept and assertive behavior in adolescents at Ar-Rudho Junior High School, East Jakarta. This study used a quantitative correlational method. The sample used in this study was all students in grades 7 to 9 totaling 156 people. The sampling technique used is random sampling. The data collection technique used in this study was a questionnaire using self-concept scale instruments and assertive behavior scales. The data analysis used in this study used the Pearson product-moment correlation test with the help of SPSS 25.0 software for Windows. The results of data analysis in this study showed a significance of 0.000 (p < 0.05), which is a relationship between self-concept and assertive behavior in adolescents. The value of the correlation coefficient that has been obtained of 0.704 (r = 0.704) can be interpreted as a relationship between self-concept and assertive behavior in adolescents, which has a potent category. That is, the higher the self-concept in adolescents, the higher the assertive behavior, and vice versa.